THE EFFECT OF AUDIT OPINION, PUBLIC ACCOUNTING FIRM’S SIZE, COMPANY SIZE, AND COMPANY PROFITABILITY TO DELAY AUDITS IN REGISTERED MANUFACTURING COMPANIES IN INDONESIA STOCK EXCHANGE IN 2015-2017 - Utami, Wikan Budi; Pardanawati, Laksmi; Septianingsih, Ika (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2018)
This study aims to determine the effect of audit opinion, Public Accounting Firm’s size, company size, and company profitability on audit delay in manufacturing goods in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2015-2017. The sample selection technique used was purposive sampling. There are several criteria that must be met by companies listed in the Indonesia Stock Exchange to be able to be sampled in this study. This research method uses multiple regression analysis which is used to determine the effect of independent variables on the dependent variable together and partially. The t test is used to test the effect of each audit opinion variable, Public Accounting Firm’s, company size, and company profitability on report lag variables. F statistic test aims to examine the effect of audit opinion variables, Public Accounting Firm’s, company size, and corporate profitability together with delay audit variables. R2 test (coefficient of determination) is done to determine how much influence the audit opinion variable, Public Accounting Firm’s, company size, and company profitability on audit delay variables. The populations of this study were 114 companies and the samples used in this study were 63 consumer goods manufacturing industry companies listed on the Indonesia Stock Exchange in 2015-2017. Data collection methods in this study use secondary data in the form of financial reports that have been published. Data is processed using SPSS 21 program. From the results of the t test, it is known that audit opinion, Public Accounting Firm’s partially has no significant effect on audit delay. Variable company size, profitability partially has a significant effect on audit delay variables. From the F test results, it is known that audit opinion, Public Accounting Firm’s, company size and profitability simultaneously have a significant effect on audit delay variables in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. Keywords : audit delay, audit opinion, Public Accounting Firm’s size, company size, company profitability.